Vitamin A regulates Akt signaling through the phospholipid fatty acid composition. Issue 10 (7th July 2017) - Pein, Helmut; Koeberle, Solveigh C.; Voelkel, Maria; Schneider, Freya; Rossi, Antonietta; Thürmer, Maria; Loeser, Konstantin; Sautebin, Lidia; Morrison, Helen; Werz, Oliver; Koeberle, Andreas
ABSTRACT: Protein kinases, including the serine/threonine kinase Akt, mediate manifold bioactivities of vitamin A, although the mechanisms behind the sustained kinase activation are diffuse. To investigate the role of cellular lipids as targetable factors in Akt signaling, we combined mass spectrometry‐based lipidomics with immunologic detection of Akt (Ser473) phosphorylation. A screening campaign revealed retinol (vitamin A alcohol) and all‐ trans retinoic acid (vitamin A acid) (RA) as hits that time‐dependently (≥24 h) deplete phosphatidylcholine‐bound polyunsaturated fatty acids (PUFA‐PCs) from NIH‐3T3 mouse fibroblasts while inducing Akt activation (EC50 ≈ 0.1–1 μM). Other mitogenic and stress‐regulated kinases were hardly affected. Organized in a coregulated phospholipid subcluster, PUFA‐PCs compensated for the RA‐induced loss of cellular PUFA‐PCs and diminished Akt activation when supplemented. The counter‐regulation of phospholipids and Akt by RA was mimicked by knockdown of lysophosphatidylcholine acyltransferase‐3 or the selective retinoid X receptor (RXR) agonist bexarotene and prevented by the selective RXR antagonist Hx531. Treatment of mice with retinol decreased the tissue ratio of PUFA‐PC and enhanced basal Akt activation preferentially in brain, which was attributed to astrocytes in dissociated cortical cultures. Together, our findings show that RA regulates the long‐term activation of Akt by changes in the phospholipid composition.—Pein, H., Koeberle, S. C., Voelkel, M., Schneider, F., Rossi, A., Thürmer, M., Loeser, K., Sautebin, L., Morrison, H., Werz, O., Koeberle, A. Vitamin A regulates Akt signaling through the phospholipid fatty acid composition. FASEB J. 31, 4566–4577 (2017). www.fasebj.org